Forgoing Medical Care because of Cost: Assessing Disparities in Health Care Access among Cancer Survivors living in the United States - Weaver, Kathryn E. (2010)
BACKGROUND: Many US cancer survivors live years after diagnosis, emphasizing the importance of health care access for survivors. It is not known if having cancer might impact disparities in health care access that are present in the general population. The objective of this study was to examine the prevalence of forgoing care due to financial concern in a representative sample of US adults to determine if cancer history and race/ethnicity are associated with likelihood of forgoing medical care. METHOD: The US National Health Interview Survey (NHIS)- 2003–2006 was used to identify 6,602 adult cancer survivors and 104,364 individuals with no history of cancer. We examined self-report of forgoing medical care services because of cost by cancer history and race/ethnicity using multivariate logistic regression. RESULTS: The prevalence of forgoing care due to cost among cancer survivors was 7.8% for medical care, 9.9% for prescription medications, 11.3% for dental care, and 2.7% for mental health care. Cancer survivors under the age of 65 years were more likely to delay or forgo all types of medical care when compared to adults without a history of cancer. Hispanic and black cancer survivors were more likely to forgo prescription medications and dental care than white survivors. Disparities among cancer survivors were largely reflective of those in the general adult population. CONCLUSIONS: More than two million US cancer survivors did not get one or more needed medical services because of financial concerns. Future research needs to examine the impact of forgoing care on survivors’ quality of life and survival.